Structural and Magnetic Properties of Co2MnSi Thin Film with a Low Damping Constant - 乔士柱 张洁 秦羽丰 郝润润 钟海 朱大鹏 康韵 康仕寿 于淑云 韩广兵 颜世申 梅良模 (中国物理快报：英文版, 2015)
Co2MnSi thin films are made by magnetron sputtering onto MgO （001） substrates. The crystalline quality is improved by increasing depositing temperature and/or annealing temperature. The sample deposited at 550℃ and subsequently annealed at 550℃ （sample I） exhibits a pseudo-epitaxial growth with partially ordered L21 phase. Sample I shows a four-fold magnetic anisotropy, in addition to a relatively weak uniaxial anisotropy. The Gilbert damping factor of sample I is smaller than 0.001, much smaller than reported ones. The possible reasons responsible for the small Gilbert damping factor are discussed, including weak spin-orbit coupling, small density of states at Fermi level, and so on.